Hypofractionated volumetric modulated arc therapy with SIB adjuvant to breast preservation surgery: retrospective experience from a Regional Cancer Centre in Eastern India. Issue 4 (29th December 2019) - Pallath, Ashwin Mohandas; Lahiri, Debarshi; Misra, Biplab; Roy, Sanjoy; Maji, Tapas; Ray, Dilip Kumar; Misra, Dillip Kumar
Abstract: Background: The incidence of breast cancer has surpassed cervical cancer in India and it has now become the most common cancer in women. Multiple randomised studies have reported low α / β value in the range of 3–4 for breast cancer, which predict a potential radiobiological advantage for hypofractionated radiotherapy resulting in such schedules becoming standard in many centers with reduction in overall treatment time. Volumetric modulated arc therapy (VMAT) is a novel technique of delivering radiotherapy that reduces treatment delivery time, requires less monitor units (MU) and offers good conformity. The mean dose to normal tissue may be minimised using this technique although there will be inferior sparing if we consider the low-dose volume such as V 5, the effect of which is not quantifiable yet. Aim: Reporting acute toxicity, cosmetic effects, and quality of life in patients of early breast cancer treated with adjuvant hypofractionated VMAT with SIB. Material and Methods: The records of 44 patients registered at the hospital between August 2014 and December 2015 were included in this analysis. Acute toxicities were analysed using CTCAE v4.03. Cosmetic outcomes were assessed using Harvard scale, while quality of life outcomes were assessed using EORTC scales and Health Related quality of life (HRQOL) questionnaires (QLQ-C30 and QLQ-BR23). Results: No grade ≥2 skin toxicities were recorded. Breast pain was recorded as Grade 1 in 13·8% patients and Grade 1 fatigue in 18·2%. The maximum haematological abnormality grade recorded was Grade 1. Cosmesis was assessed at the baseline, 6 months, 1 year and 2 years. A total of 88·6% of the patients had an Excellent or good cosmesis at the baseline, which was similar even at 6 months, at 88·7%, improved further at 1 year to 90·9%. At 6 months post radiotherapy, high functional scale QOL scores were noted. Conclusion: The technique is associated with minimum acute toxicity, good to excellent cosmesis and acceptable quality of life.